2021
DOI: 10.1155/2021/8874834
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Associated Factors of Depression among Admitted Adult Patients in Surgical and Medical Wards of Saint Paul’s Hospital Millennium Medical College, Addis Ababa, Ethiopia

Abstract: Background. Depression is a leading cause of major public health problems globally, and its prevalence has been increasing, particularly in low- and middle-income countries including our country. Therefore, this study is aimed at exploring depression symptoms and their determinants among admitted medical and surgical patients which is important to get optimal care for patients. Methods. An institution-based cross-sectional study was conducted from May to June 2019, on adults’ medical and surgical admitted pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
1
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 37 publications
(32 reference statements)
2
1
1
Order By: Relevance
“…Being a widower or widowed and divorced was greater than three times more likely to have depression. This was consistent with other studies carried out in other parts [ 30 , 31 ], china [ 34 ] and Uganda [ 35 ]. The possible explanation might be Divorce and widowed are associated with significant risk of emotional distress, including clinically-significant psychological depression the reason might also be the sociocultural attitude and norms of less respecting the divorced and widowed, being single has also psychological impact, probability of losing the next chance of marriage.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Being a widower or widowed and divorced was greater than three times more likely to have depression. This was consistent with other studies carried out in other parts [ 30 , 31 ], china [ 34 ] and Uganda [ 35 ]. The possible explanation might be Divorce and widowed are associated with significant risk of emotional distress, including clinically-significant psychological depression the reason might also be the sociocultural attitude and norms of less respecting the divorced and widowed, being single has also psychological impact, probability of losing the next chance of marriage.…”
Section: Discussionsupporting
confidence: 93%
“…Respondents with history of poor social support, in our study were another significant factor to develop depression. This result was supported by other studies in Berlin [ 30 ] and Germany [ 39 ]. The possible explanation could be being scheduled for surgery is stressful condition in which they might think of morbidity and mortality so, patients need strong social support both in psychological makeup and resource.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…of depression (21). As different studies showed symptoms and frequency of depression differ between societies' backgrounds, and these are thought to be associated with cultural, genetic, and environmental factors (22).…”
Section: Introductionmentioning
confidence: 99%